Research avenues for amplifying Indigenous radio [version 1; peer review: 2 approved] - Katie Moylan (Open Research Europe, 2022)
In this article, I discuss Indigenous radio’s ongoing importance for tribal communities in the US from my perspective as a settler scholar, drawing on multifaceted research into Indigenous radio’s programme content and production practices before and during the pandemic. For this research, ‘Indigenous radio’ refers to radio produced, managed, presented and/ or owned by tribal communities. Other terms in use to describe Indigenous radio include Native American, Indian, or tribal radio, demonstrating that there is not a single universalising term and reflecting a diversity in tribal cultures, languages and practices more generally. Building on this understanding of the inherent diversity of Indigenous radio, I describe the ways in which my overarching research project investigates Indigenous radio holistically, via critical outputs combining a literature review of Indigenous theoretical approaches, an online interactive map of tribal stations and in-depth case studies of tribal stations. Through these, I explore community-building practices of Indigenous radio as produced through what Indigenous theorists Glen Coulthard and Leanne Betasamosake Simpson (2016) term grounded normativity. Building on this avenue of exploration, I suggest the place-based values embedded in Indigenous radio production practices and content can function as everyday acts of resurgence, following Jeff Corntassel’s (2012) conceptualisation of ways in which Indigenous resurgence can reinforce a project of decolonisation. To exemplify and situate these arguments, I draw on examples of radio production and practitioner insights from selected tribal stations embodying diverse tribal production practices and content, before turning to focus on pandemic practices in Indigenous radio. When the pandemic emerged, my research focus necessarily widened to include and examine COVID-related practices and programming in tribal radio, enabling reflection on these in the context of a paradigm shift in which the value of tribal radio's community-building work has become acute.